Transnational Education: Looking at Out- and Inflow of International Student Migration - Ika Sandra (Jurusan Ilmu Sosial Politik Fakultas Ilmu Sosial Universitas Negeri Padang, 2020)
The interest of students from various countries to study overseas have been increasing lately, resulting in a global trend. Their reasons could be different from one another. This study analysed student migration using different models and theories. Through qualitative research, using literary and ethnographic analysis along with transnational perspectives, this project analyzed the reasons behind student’s migration. The finding indicates that different theories and approaches show different reasons why the students migrate. Push-pull factor theory shows that factors from the home country and the host country can count as reasons for why students study abroad. World system theory shows how economically, politically, and socially powerful countries play an important role in attracting international students. The demand and supply models are related to the middle class who are eager to gain cultural and social capital through studying abroad. Finally, the global space approach has three poles to look at international student flows; one of which is the Pacific pole where English-speaking countries become popular destinations particularly among international students from Asian countries. This article suggests that if host countries want to market their education comprehensively, the host countries should give more space and easy access for the home countries of the outflows of student migration.